Peran M. Arsjad Th. Lubis dalam Pengembangan Ilmu-Ilmu Keislaman - Ja'far Ja'far (IAIN Ponorogo, 2020)
Abstract: This study aims to analyze the role of M. Arsjad Th. Lubis in the development of Islamic sciences. This article is the result of a library research using a historical approach, to be precise intellectual history. This study has succeeded in showing that Tuan Arsjad is a scholar who has helped develop Islamic sciences in Indonesia, especially in North Sumatra. His works cover the extents of the Qur’an, hadith, theology, comparative religion, Islamic law and history. All of his works before and after independence were responses to the problems of the people and nation that occurred during his lifetime. His pre-independence works focused on comparative studies of religions, and his works in this field were his response to Christianization activities in North Sumatra. After independence, Tuan Arsjad became a very productive scholar. His works in the fields of the Qur’an, hadith, theology and Islamic law are used by hundreds of madrassas that managed by Al Washliyah, and his works in the field of comparative religion are read by preachers when preaching in Muslim minority areas in North Sumatra. A number of his books have also been translated into various regional languages and distributed free of charge to converts. His works in the field of fiqh siyasah (politics) are a response to the Old Order's policies towards a number of political upheavals in the regions. All of this shows that Tuan Arsjad’s presence has contributed to social change in Indonesia, particularly North Sumatra.الملخص: هذه الدراسة تهدف إلى تحليل مساهمة السيد محمد أرشد طالب لوبيس في تطوير العلوم الإسلامية. وهذه المقالة هي نتيجة الدراسة المكتبة باستخدام مقاربة التاريخية الفكرية. لقد دلت هذه الدراسة بعد بحثها على أن السيد أرشد عالم ساعد في تطوير العلوم الإسلامية في إندونيسيا عامة و في سومطرة الشمالية خاصة. وتضمنت أعماله في مجالات متعددة فيها علوم القرآن والحديث وعلم الكلام ومقارن الأديان وكذالك في مجال الأحكام الشريعة والتاريخ الإسلامية. كانت جميع أعماله ما قبل الاستقلال وما بعده استجابا لمشاكل الشعب والأمة التي حدثت في حياتهم. وكان دراسته التي تتركزت في مجال مقارنة الأديان استجابة لأنشطة الدعوة المسيحية في سومطرة الشمالية. وكان بعد الاستقلال أصبح السيد أرشد باحثًا منتجًا للغاية. تستخدم أعماله في مجالات القرآن والحديث وعلم الكلام والشريعة الإسلامية حوالى مئات المدارس الدينية الوصلية. وكان كتابه في مجال مقارنة الأديان يقرأ كثير من الدعاة عند دعوتهم في دائرة الأقليات المسلمة في سومطرة الشمالية. وكان عدد من كتب السيد أرشد وقد تُرجم إلى لغات إقليمية مختلفة ووزعتها مجانًا للمؤلفين. وكذلك كتابه في مجال السياسة هي رد فعل لسياسات النظام القديم التي تتجه عدد من الاضطرابات للسياسية المحلية. وكل هذا يدل على أن السيد أرشاد قد ساهم مساهمة كبيرة في التغيير الاجتماعي في إندونيسيا ، ولا سيما سومطرة الشمالية.Abstrak: Studi ini bertujuan untuk menganalisa peran M. Arsjad Th. Lubis dalam pengembangan ilmu-ilmu keislaman. Artikel ini merupakan hasil sebuah studi kepustakaan dengan menggunakan pendekatan sejarah, tepatnya sejarah intelektual. Studi ini berhasil menunjukkan bahwa Tuan Arsjad merupakan ulama yang turut mengembangkan ilmu-ilmu keislaman di Indonesia, khususnya di Sumatera Utara. Karya-karyanya mencakup bidang Alquran, hadis, teologi, perbandingan agama, hukum dan sejarah. Seluruh karyanya sebelum dan sesudah kemerdekaan merupakan respons terhadap persoalan umat dan bangsa yang terjadi di masa hidupnya. Karya-karyanya sebelum era kemerdekaan terfokus pada kajian perbandingan agama, dan karya-karya dalam bidang ini merupakan responsnya terhadap aktivitas kristenisasi di Sumatera Utara. Pasca kemerdekaan, Tuan Arsjad menjadi ulama yang sangat produktif. Karyanya dalam bidang Alquran, hadis, teologi dan hukum Islam digunakan oleh ratusan madrasah yang dikelola Al Washliyah, dan karya-karyanya dalam bidang perbandingan agama menjadi bacaan para mubalig saat melakukan dakwah di kawasan minoritas Muslim di Sumatera Utara. Sejumlah bukunya juga telah diterjemahkan ke berbagai bahasa daerah dan dibagikan secara gratis untuk para mualaf. Karya-karyanya dalam bidang fikih siyasah (politik) merupakan responsnya terhadap kebijakan Orde Lama terhadap sejumlah pergolakan politik di daerah. Semua ini menunjukkan bahwa kehadiran Tuan Arsjad telah turut memberikan kontribusi dalam perubahan sosial di Indonesia, khususnya Sumatera Utara.